Associations of sleep and individual characteristics with accelerometer-measured catch-up sleep among older employees - Myllyntausta Saana; Kronholm Erkki; Pulakka Anna; Pentti Jaana; Virtanen Marianna; Stenholm Sari (Elsevier B.V., 2025)
There is limited knowledge on the characteristics of employees who engage in catch-up sleep, the extension of sleep duration on free days to compensate for sleep loss accumulating during workdays. This study examined associations of accelerometer-measured free day catch-up sleep with sleep duration, sleep timing, and socio-demographic, health and lifestyle factors among older employees. We measured sleep repeatedly with accelerometers among 824 public sector employees in Finland (mean age 63 years; 86% women). On average, the participants provided 1.7 annual accelerometer measurements and 1,437 person-observations in total. Catch-up sleep was defined as longer average sleep duration on free days compared with average sleep duration on workdays. Prevalence of catch-up sleep was 78%. On average, the catch-up sleep group extended their sleep on free days by 1 hour 22 min (95% confidence interval [CI] 1 h 19 min – 1 h 26 min), whereas the non-catch-up sleep group reduced their sleep duration by 45 min (95% CI -50 min – -40 min). Catch-up sleep was mainly associated with delayed awakening time on free days (by 1 h 57 min, 95% CI 1 h 52 min – 2 h 2 min). We also observed a greater social jetlag in the catch-up sleep group in comparison to the non-catch-up sleep group, whereas no differences were observed in chronotype, self-reported sleep, or other individual characteristic. In conclusion, accelerometer-measured catch-up sleep is common among older employees in Finland and major differences in duration and timing of sleep occur between those with and without catch-up sleep.